Agricultural productivity in Burkina Faso: The role of gender and risk attitudes - Mohammad H. Sepahvand (Uppsala University, Department of Economics, 2019)
This study is an empirical investigation of how individual risk attitudes influence the agricultural productivity of men and women in a sub-Saharan African country, Burkina Faso. By analyzing a large representative panel survey of farmers from 2014 and 2015, the results indicate lower productivity on female-owned plots. Controlling for various socio-economic factors, the results show that as the female farmers' increase risk taking, the productivity of female-owned plots goes down. These results are robust regarding alternative specifications. However, productivity differences vary by the type of crop cultivated, the agro-ecological zone, the share of female farmers in the region, the soil quality, type of seed used, and between consumption quantiles when comparing the poorest to the richest 20 per cent of the farm households. The results indicate that female farmers do not increase their plot yield by taking more risk. It is argued that agricultural policy interventions in Burkina Faso need to be gender sensitized when addressing issues related to credit constraints, improved inputs, and policies that support increase in productivity.
urn:nbn:se:uu:diva-377047
Keywords: D13; D81; J16; Q12; 330; risk attitudes; gender differences; agriculture; productivity; sub-Saharan Africa; Burkina Faso